C-MEDS: COMMUNITY MEDICATION EDUCATION, DATA, AND SAFETY PROGRAM. (11th November 2018) - Meyer, M; Batra, R; Likar, D; Enguidanos, S
Abstract: C-MEDS is a brief, customized medication safety and management intervention delivered in-home by a team of geriatric experts (pharmacists, nurses, and pharmacy technicians). We enrolled 104 diverse older adults. Among these, 68% were female and the mean age was 72 (SD=8.5). Number of routine prescription medications taken ranged from 3 to 24, with an average of 9 (SD=4.2). Nearly half (47%) of participants lacked prerequisite cognition/literacy, 53% had one or more ER visits and 43% had one or more falls in the previous 6 months. More than 1, 500 medications related problems were identified. About 13% of these problems were related to adherence issues; 46% to safety issues; 15% to lack of patient/caregiver skills or knowledge in drug administration; and 8.5% were actual or potential drug interaction, duplication, or side effects. Interventions were most successful when patients and caregivers were receptive to receiving help and instruction in medication management.